29. SURVEY ON THE SATISFACTION OF OUTPATIENT AT THE DEPARTMENT OF TRADITIONAL MEDICINE SAINT PAUL GENERAL HOSPITAL IN 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the satisfaction of and some factors at the Department of Traditional Medicine – Saint Paul General Hospital in 2022Subjects and Methods: Cross-sectional descriptive study of 330 outpatients treated at the Department of Traditional Medicine – Saint Paul General Hospital from July 2022 to December 2022.Results: The overall patient satisfaction rate was 84.5%, the highest satisfaction score for the treatment cost factor was 4.84 ± 0.28 and the lowest for the waiting time factor was 4.24 ± 0.69. The average satisfaction score for the factors of procedures - processes, facilities, and medical staff were 4.69 ± 0.39, 4.65 ± 0.27, 4.80 ± 0.25, respectively.Conclusion: Most patients are satisfied with the quality of expertise and services when receiving outpatient at the Department of Traditional Medicine.
Keywords: Satisfaction; Outpatient; Faculty of Traditional Medicine.